PENGARUH ETIKA AUDITOR, PENGALAMAN AUDITOR, FEE AUDIT, DAN MOTIVASI AUDITOR TERHADAP KUALITAS AUDIT (Studi pada Auditor KAP di Semarang) - Andreani Hanjani; Rahardja Rahardja (Diponegoro Journal of Accounting, 2014)
In the era of globalization today, the demands of society towards a quality auditor has increased over time. Auditors must consider ethical profession in various decision making. In addition, experience, audit fee, and motivation can also improve competencies in decision making. The aim of this research is to test the influence of ethics the auditors, the experience of auditors, audit fees and motivation audit the auditors against the quality of an audit. The population of this research are all an auditor who work in the office of the public accountant in the city of Semarang. Sampling method used is convenience sampling. The Data used in this research is the primary data, that is done using the method of survey with questionnaire. Processing method used is multiple regression analysis. The results showed that the ethics of the auditor, the audit fee, auditor experience and motivation of Auditors significant and positive impact on the quality of audits.